Ilchamus pastoralists' indigenous knowledge and its use in coping with and adapting to climate change in Marigat, Kenya - Lenachuru, Clement Isaiah, author; Fernandez-Gimenez, Maria, advisor; Reid, Robin, advisor; Galvin, Kathleen, committee member; Meiman, Paul, committee member (Colorado State University. Libraries, 2016)
In view of present and future changes in weather and climate, documenting how pastoralists use their indigenous knowledge (IK) in coping with and adapting to climate change in their localities is increasingly important, as this knowledge may inform climate adaptation policies and practices. The objectives of this dissertation are: 1) to document the Ilchamus pastoralist IK about weather and climate, including indicators of environmental change; 2) to establish how the Ilchamus acquire, share and transmit their IK over generations and within their community; and 3) to investigate how their IK informs Ilchamus decision-making in their livelihood production systems. To address these objectives, I conducted focus groups discussions with men and women in four communities, and administered a household questionnaire to 331 households in Marigat Sub-County, Kenya in 2010 and 2011. I found that the Ilchamus possess rich local knowledge on weather and climate, and use a variety of physical and biological indicators to detect environmental change. They observe changes in many of these indicators, and attribute many of these changes to climate change. Ilchamus obtain their indigenous knowledge through interactions with the biophysical environment, and from a variety of other traditional and non-traditional sources within the community. Ilchamus community members also use a number of formal information sources about weather and climate, including radio and television. Indigenous knowledge is not evenly distributed in the community, and Ilchamus often consult local experts in addition to using their experiential knowledge. Use of traditional and formal sources of knowledge varies with age and education level. Community elders and those with less formal education rely more on traditional knowledge sources while younger and members that are more educated more often use formal sources of information. Ilchamus IK is passed from parents to children though daily interactions and folklore, and is shared within the community through social networks and organizational structures. Although there are many social structures through which knowledge is shared, most of them are exclusive to men. Women are therefore disadvantaged in that only one informal social network is available to them, and this network is task-specific and short term. Traditional means of IK transfer remain intact, but face a challenge from young and educated members of the community, who disregard or dismiss IK and value foreign cultures and practices over local traditions and lifestyles. Ilchamus elders complain of formal education eroding their culture. However, the elders also support formal education for the community’s children, which they see as providing more livelihood options for the future, beyond pastoralism. Ilchamus use a number of customary coping and adaptation strategies to deal with a variable and changing climate. They are aware of the possible consequences of climate change on their production systems and make livelihood decisions based on this knowledge coupled with their experience. However, the majority fail to take timely action in response to changing conditions. This study demonstrates that Ilchamus community members hold extensive indigenous knowledge of weather and climate and that this knowledge has been used over time to inform livelihood decision-making in the community. I therefore recommend the Ilchamus indigenous knowledge system to be recognized by scientists and policy makers for its potential value in adaptation to climate change.